Capturing Climate Change Online Discourse to Support agriculture Research - Wijaya Toni; Bakti Dadang Karya; Agung Pratama Maulana; Ali Suprihatin (BIO Web of Conferences)
This study investigates the changing conversation around climate change on social media in Indonesia, specifically analysing the time frame from January to May 2024. Given the ongoing and substantial risks that climate change presents to countries, communities, and people, it is crucial to comprehend how the public perceives and discusses this pressing matter. We collect data from social media platforms and the Scopus research database. Then employing a deliberate scraping method to gather 2,300 tweets that had hashtags and keyword linked to “PerubahanIklim” or “climate change”. After the first dataset was obtained, the preparation step progressed to the preprocessing phase. This comprehensive methodology enables a detailed comprehension of the progression of climate change discourse on social media in Indonesia. The research also emphasises the fluidity of climate change discourse, illustrating the transformation of public opinion and involvement with the subject during the five-month study period. This study adds to the expanding corpus of research on climate change communication in social media settings, specifically focusing on developing countries. Through a comprehensive examination of online conversations in Indonesia, we present significant observations for politicians, environmental organisations, and researchers aiming to comprehend and tackle climate change issues in the area.